Low Income Community as Crowd Worker for Crowdsourcing: Issues, Challenges and Future Direction - Zakariah, Zazaleena; Janom, Norjansalika; Habibah Arshad, Noor (International Journal of Engineering and Technology, 2018)
World are now facing flood of low income community responding to current global issue regarding employment. Considering the advantages of crowdsourcing, it has been identified as one potential solution to the issue. Responding to that, the concept has been implemented in many developing countries that have high rate of low income community such as India, Nepal and Philippines. Through crowdsourcing, business and individual can achieve greater and higher productivity in faster and shorter period. Crowdsourcing offer flexibility in terms of time, locations and durations of doing tasks and the most important is crowdsourcing will give additional income to complement existing income that will help to uplift oneâ€™s lifestyle hence reduce the rate of low income community. However, focusing on low income community as crowd worker for crowdsourcing require depth understanding on varies factors such as crowd education levels, skills, attitudes, language and etcetera. Visibly, there are numerous issues and challenges in the implementation process. Thus, this study aims to discuss the issues and challenges when dealing with low income community as crowd worker. This study presents seven vital factors that need to be taken into deliberation when dealing with low income community. The results and discussion from this study can be used as a road map to prepare an action plan for a successful crowdsourcing implementation for low income community.Â Â